Women Leaders and the Governance Revolution in Villages - Bariroh, Laili; Ilmiyah, Dakhirotul; Laviola, Zuvia (UIN Sunan Ampel Surabaya, 2024)
This study examines the role of women leaders in transforming village governance amidst the dominance of patriarchal culture. The primary objective is to uncover the experiences and leadership strategies employed by women in implementing significant changes within rural communities. Utilizing a qualitative method with descriptive analysis, data were collected through in-depth interviews with the village head, local officials, and residents of Metatu village. By adopting postcolonial feminist theory as an analytical framework, this research highlights the social, cultural, and structural challenges faced by women leaders. The findings reveal that they have implemented the digitalization of public services, enhanced community participation, and leveraged Village-Owned Enterprises (BUMDes) to increase local revenue (PAD). Despite employing transformational leadership strategies based on collaboration and effective communication, women leaders continue to face resistance and encounter a double bind in decision-making processes. These findings underscore the necessity of structural support and policy reforms to optimize the role of women in village governance